Analyzing the effect of physical exercise on subjective well-being of university students using the chain mediation model - Wei Liu; Zichao Li; Hongbo Zhao (Scientific Reports)
Abstract Subjective well-being is one of the important factors affecting the mental health of college students, and although studies have proven the effectiveness of physical exercise on subjective well-being, the mechanism of the influence of physical exercise on subjective well-being has yet to be studied in depth. Therefore, this study constructed a mechanism model of the influence of physical activity on college students‘ subjective well-being, and used the Physical Activity Scale, Subjective Well-being Scale, Mental Toughness Scale, and Stress Perception Scale to investigate 600 college students, and examined the chain mediating role of mental toughness and stress perception in the relationship between physical activity and college students’ subjective well-being. It was found that (1) there is a significant correlation between physical exercise, mental toughness, stress perception, and college students‘ subjective well-being; (2) mental toughness and stress perception mediate between physical exercise and college students’ subjective well-being; and (3) mental toughness and stress perception chain mediate between physical exercise and subjective well-being. This result suggests that mental toughness and perceived stress not only play independent roles but also chain-mediated roles between physical activity and college students’ subjective well-being.